The Indonesian National Police's Strategy in Combating Artificial Intelligence-Based Digital Content Manipulation as a Means of Political Crime and Cyber Fraud in Indonesia - Adrian Batubara; Vita Mayastinasari; Kif Aminanto (Indonesian Journal Publisher, 2026)
The development of Artificial Intelligence has given rise to new forms of cybercrime through deepfake-based digital content manipulation, voice cloning, synthetic media, and AI-generated content, which are used as a means of political crime and cyber fraud in Indonesia. This study aims to analyze problems in law enforcement, weaknesses in the Indonesian National Police’s strategy, and legal reforms in addressing artificial intelligence (AI)-based digital content manipulation through strengthening smart policing and cyber resilience. This study employs a normative juridical method with a legislative and conceptual approach, through the analysis of various regulations, legal theories, and doctrines related to cybercrime, artificial intelligence, and national cybersecurity. The results reveal that law enforcement against AI-based digital content manipulation still faces several weaknesses, including the absence of specific legal norms related to AI crimes and political deepfakes, limited capacity in cyber policing and digital forensics, weak coordination between institutions, and low public digital literacy. The Indonesian National Police's strategy is still reactive and has not been optimal in implementing artificial intelligence-based predictive policing. Therefore, legal reform is needed through the establishment of specific regulations for Artificial Intelligence Crime, strengthening AI forensic and cyber intelligence units, developing an integrated cybersecurity system, and developing smart policing and cyber resilience to create an adaptive, responsive, and sustainable cyber law enforcement system in the era of digital transformation.